Screening test for detection of Newcastle Disease, Avian Influenza and Infectious Bronchitis viruses using multiplex reverse transcriptase polymerase chain reaction approach - Hartawan R; DharmayantI NLPI (Indonesian Center for Animal Research and Development (ICARD), 2013)
Numerous viral pathogens are circulated in the environment of commercial chicken farms that causing the difficulty in the confirmation of diagnosis. A breakthrough on the diagnosis technique is required in order to deal with multiple viral infections. Ideally, the approach should have not only high accuracy but also economical and straightforward. The objective of this research is to develop a rapid multiplex reverse transcriptase polymerase chain reaction (mRT-PCR) diagnostic method for three common infectious viral diseases in poultry, Newcastle Disease (ND), Avian Influenza (AI) subtype H5N1 and Infectious Bronchitis (IB). This study was successful in developing and optimizing the mRT-PCR for these three pathogens in a single reaction test. Testing 67 field samples from Sukabumi district revealed the presence of several targeted viruses. Key Words: Screening Test, Multiplex RT-PCR, Newcastle Disease, Avian Influenza, Infectious Bronchitis